2009
DOI: 10.1213/ane.0b013e31819dcd08
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Peripherally Administered CDP-Choline in an Acute Inflammatory Pain Model: The Role of α7 Nicotinic Acetylcholine Receptor

Abstract: The results of this study suggest that intraplantar CDP-choline has antihypersensitivity and antiinflammatory effects mediated via alpha7nAChRs in the carrageenan-induced inflammatory pain model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 33 publications
1
31
0
1
Order By: Relevance
“…Peripheral (intraplantar) application of nicotinic agonists selective for the α4β2 or α7 subtype is antinociceptive [19,58,59]. Nicotinic receptors on peripheral terminals may contribute to these effects, although direct evidence for this is lacking.…”
Section: Neural Substrates For Nachr-dependent Analgesiamentioning
confidence: 99%
“…Peripheral (intraplantar) application of nicotinic agonists selective for the α4β2 or α7 subtype is antinociceptive [19,58,59]. Nicotinic receptors on peripheral terminals may contribute to these effects, although direct evidence for this is lacking.…”
Section: Neural Substrates For Nachr-dependent Analgesiamentioning
confidence: 99%
“…These receptors are also present on immune and nonimmune cytokine-producing cells, including macrophages and keratinocytes (Wang and Wang, 2003;Pavlov and Tracey, 2004). Furthermore, a7 nAChR agonists, such as choline, CDP-choline, compound B, JN403 [(S)-(1-azabicyclo [2.2.2]oct-3-yl)-carbamic acid (S)-1-(2-fluoro-phenyl)-ethyl ester], and (2)-spiro[1-azabicyclo[2.2.2]octane-3,59-oxazolidin]-29-one (AR-R17779, exhibited anti-inflammatory effects in various inflammation and pain models in rodents (Damaj et al, 2000;Medhurst et al, 2008;Feuerbach et al, 2009;Gurun et al, 2009;van Maanen et al, 2009;Rowley et al, 2010;Marrero et al, 2011;Munro et al, 2012). Although a7 nAChR agonists showed beneficial effects in inflammatory animal models in some studies, these effects were not seen consistently in other studies (Gao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds enter the circulation and are taken up into the cells and utilized for intracellular enzymatic resynthesis of CDP-choline [6]; it has been shown that most of the effects of exogenously administered CDP-choline are mediated by its choline, and thereby acetylcholine (ACh), component [5,7]. We recently demonstrated that central and peripheral injection of CDP-choline induced dose-dependent and time-dependent antinociceptive effects in acute, inflammatory, and chronic constriction injury (CCI) models of neuropathic pain in rats without any motor impairment [8][9][10][11]. In addition, our previous studies showed that centrally administered CDP-choline elicited an analgesic effect through central cholinergic and opioidergic systems [8,9,11].…”
Section: Introductionmentioning
confidence: 99%